Transition to motherhood and mothering for women in wheelchairs: a nursing perspective - Livia Fajin de Mello dos Santos; Janaína Pinto Janini; Viviane de Melo Souza; Rosângela da Silva Santos (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To discuss the process of transition to motherhood and mothering of women who are wheelchair users, from the perspective of Afaf Ibrahim Meleis. Method: Qualitative, descriptive, exploratory study conducted with six women in the state of Rio de Janeiro. The Life Narrative method was used, with thematic analysis in the light of Transitions Theory. Results: Developmental and situational transitions occurred and were influenced by personal, community and social factor. Moved mainly by ignorance and prejudice of family members and of the social network, these factors were not barriers for motherhood and mothering. Final Considerations: The reproductive rights of women with disabilities must be respected and, for this, inclusive policies focused on women with disabilities should be adopted.